2001
DOI: 10.1182/blood.v97.4.1092
|View full text |Cite
|
Sign up to set email alerts
|

Transcobalamin codon 259 polymorphism in HT-29 and Caco-2 cells and in Caucasians: relation to transcobalamin and homocysteine concentration in blood

Abstract: Transcobalamin (TC) is the plasma transporter that delivers vitamin B(12) to cells. We have already reported that HT-29 and Caco-2 cells secrete different TC variants. HT-29 secretes 2 TC isoproteins (codon 259-Pro/Arg [259-P/R]), exhibiting unequal concentrations (TC 259-P > TC 259-R), and Caco-2 cells only secrete the phenotype 259-R. We investigated the relation between phenotypic and genetic TC polymorphism in HT-29 cells transfected with Caco-2 TC complementary DNA and in 159 healthy Caucasians. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 29 publications
11
90
2
2
Order By: Relevance
“…Previous studies, however, did not find an association between this polymorphism and either holotranscolbalamin [41] or Hcy [38,42]. Furthermore, an increase in Hcy concentration was shown to be associated with the heterozygous TCN2 776 CG genotype when compared to the homozygous genotypes [36]. The discrepancy between these studies may be the result of several variables, such as differences in age, ethnicity, gender of the study subjects, folate intake, vitamin B 12 and B 6 intakes, genetic factors, and study design [4,43,44].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previous studies, however, did not find an association between this polymorphism and either holotranscolbalamin [41] or Hcy [38,42]. Furthermore, an increase in Hcy concentration was shown to be associated with the heterozygous TCN2 776 CG genotype when compared to the homozygous genotypes [36]. The discrepancy between these studies may be the result of several variables, such as differences in age, ethnicity, gender of the study subjects, folate intake, vitamin B 12 and B 6 intakes, genetic factors, and study design [4,43,44].…”
Section: Discussionmentioning
confidence: 66%
“…Previously published data show that the TCN2 776 G allele is associated with decreased transcription and decreased concentrations of cellular and plasma transcobalamin, the carrier protein that delivers vitamin B 12 to cells [36]. This suggests [36][37][38] in addition to increased MMA [39] and Hcy concentrations [37,40]. Previous studies, however, did not find an association between this polymorphism and either holotranscolbalamin [41] or Hcy [38,42].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The following enzymes play the key role in this process: MTHFR, MTR, MTRR, and TCN II [12,13,[21][22][23][24][25][26][27][28][29][30]. таких пациентов генетического исследования, направлен-ного на поиск тромбофилий.…”
Section: генетические предикторы прогноза при ибсunclassified
“…Zetterberg et al (2003) contends that the transcobalamin codon 259 polymorphism should be designated 776C>G, not 775G>C as the polymorphism is a C-to-G substitution at position 776 in relation to the first nucleotide (+1) of the ATG-translation initiation codon, not a G-to-C substitution at nucleotide 775 [31]. Namour et al [32] reported a frequency of 34.6% for C homozygotes, 47.8% for heterozygotes, and 17.6% for G homozygotes among healthy Caucasians. Heterozygotes 259 P/R were found to have significantly higher plasma homocysteine concentration than homozygotes 259-R and 259-P.…”
Section: Transcobalamin IImentioning
confidence: 99%